Investigation of coriolis coupling effect on the ND plus D reaction - Hekim, Seda; Akpinar, Sinan (Elsevier, 2018)
We present time dependent quantum wave packet calculations for the ND (a(1)Delta)+ D (S-2) reaction on the modified NH2(A) over tilde (2) A(1) potential energy surface using the real wave packet and flux analysis methods. Initialstate-resolved reaction probabilities, cross sections and rate constants were obtained taking into account the Coriolis Coupling (CC). The significance of including the CC quantum scattering calculations has been revealed by the comparison between the CC and the Centrifugal Sudden (CS) approximation calculation. The calculated thermal reaction rate constant is in a good agreement with the available experimental data and semiclassical results. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Potential-Energy Surface; Quantum Wave-Packet; Renner-Teller; N(D-2)+H-2 Reaction; Dynamics; Accurate; State; Nh2